Zerbait gehiago euskal azentubideen historiaz - Hualde, José Ignacio (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1997)
In this paper the origin of the diversification of the Basque accentual systems of the western and central areas is considered. In spite of the great accentual diversity found in this area, certain agreements on the accentual properties of specific morphological categories and lexical items clearly point out to a common origin in the not too distant past. Although the most common accentual pattern in this territory is postinitial accent, I argue that the original system must have had phrase-final accentuation, like some ofthe present-day varieties of the Bizkaian coast. It appears that the development form phrase-final to postinitial accent, has followed one of two different paths, depending on the area. A direct transformation from one accentual system into the other would have been the association ofaccentual prominence with a rise in pitch (as it normally is in Spanish), instead of with a pitch fall, as in coastal Bizkaian. A more complex route was followed in some other areas going through stages with penultimate and postpostinitial accent, both of which are attested in neighboring present-day varieties.